Electronic structure and magnetic properties of the strong-rung spin-1 ladder compound Rb3Ni2(NO3)7 - Pchelkina, Zlata V.; Werner, Johannes; Koo, Changhyun; Klingeler, Rüdiger (Physical review, 2018)
Rb3Ni2(NO3)7 was obtained by crystallization from anhydrous nitric acid solution of rubidium nitrate and nickel nitrate hexahydrate. The crystal structure determined on single crystals implies isolated spin-1 two-leg ladders of Ni2+ ions connected by (NO3)− groups as basic elements. Magnetic susceptibility, specific heat in magnetic fields up to 9 T, magnetization, and high-frequency electron spin resonance studies performed on powder samples show the absence of long-range magnetic order at T≥2 K. Electronic structure calculations and the detailed analysis of the experimental data enable quantitative estimates of the relevant parameters of the S=1 ladders in Rb3Ni2(NO3)7. The rung coupling J1=10.16 K, the leg coupling J2=1.5 K, and the Ising-type anisotropy |A|=8.6 K are obtained. The scenario of a valence-bond solidlike quantum ground state realized in the two-leg Ni2+ ladders is further corroborated by model simulations of the magnetic susceptibility.
Die Ziffern 3, 2, 3 und 7 in Rb3Ni2(NO3)7 sind tiefgestellt
Gesehen am 10.02.2020